Mean Satisfaction Scores in Patients Wearing Removable Dental Prosthesis According to Oral Health Index Profile-14 : Satisfaction of Patients with Dental Prosthesis - Mansur, Aamna; Waqar, Hanzala; Ullah, Hanif; Syed, Aamir; Ullah, Haseeb; Ullah, Sami (Pakistan BioMedical Journal, 2024)
Removable dental prosthetics, also known dentures, are used to restore function, appearance, and phonation after tooth loss. However, the majority of people who wear dentures are not satisfied with them. Objective: To assess the mean fulfillment score of patients utilizing removable denture prosthesis as per oral health index record profile-14 (OHIP-14). Methods: A cross-sectional descriptive study was conducted at the Department of Prosthodontics, Bacha Khan Medical College, Mardan from 5th November 2020 to 25th May 2021. A total of 272 participants of both gender with ages between 20 to 70 years, wearing acrylic removable partial denture in or the two arches for something like one year, and had no indications of pathology in leftover teeth were enrolled in this study. OHIP-14 examiner was utilized to gauge the factors of fulfillment with removable dental prosthesis. OHIP-14 scores were stratified among age groups and gender to see effect modifiers. The data were analyzed using SPSS 26.0. Results: The mean age of the participants in the study was. 53.28±10.997 years. The mean OHIP-score was 23.63±7.095. The mean OHIP-score in males was 23.34±6.641 and in females was 23.91±7.523. The difference in OHIP-14 score was not statistically significant (p=0.51). The highest mean OHIP-14 score was present in age group 20-30 years (25.20±5.673) followed by age group 61-70 years (24.27±7.290). The lowest OHIP-14 score was in age group 22.57±6.448 years. Conclusions: The average OHIP-14 score is lower, which further indicates reduced satisfaction with removable partial dentures. Age and gender had little impact on how satisfied people were with removable partial dentures.<span class="EOP SCXW93043107 BCX0" data-ccp-props="{"134233279":true,"201341983":0,"335551550":6,"335551620":6,"335559739":0,"335559740":240,"335572071":0,"335572072":0,"335572073":0,"335572075":0,"335572076":0,"335572077":0,"335572079":0,"335572080":0,"335572081":0,"335572083":0,"335572084":0,"335572085":0,"335572087":0,"335572088":0,"335572089":0,"469789798":"nil","469789802":"nil","469789806":"nil","469789810":"nil","469789814":"nil"}">